Comparative Study between Recycled Fine and Coarse Aggregate Used in Roller Compacted Concrete Pavement (Journal of Engineering, 2023)
To decrease the impact on the environment of building waste, the recycled aggregate may be used in various sustainable engineering applications, such as roller compacted concrete pavement (RCCP). This research examined how using recycled aggregate as a partial replacement for natural aggregate as coarse or fine affected the mechanical properties of roller-compacted concrete pavement. The recycled aggregate was crushed and sieved to coarse and fine aggregate before being used in the roller-compacted concrete pavement. Compressive strength, splitting tensile strength, and flexural strength were all evaluated after the samples were prepared at 28 and 90 days of curing. According to the study's findings, the partial replacement of coarse or fine aggregate with recycled aggregate by (10, 15 and 20%) by volume resulted in decreasing the mechanical properties and increasing the absorption and porosity of RCCP due to the contaminated cement paste on the surface of RCA when compared to the reference mix made with natural aggregate. Because the recycled aggregate contains un-hydrated cement particles, the results have improved after 90 days.